Analisis Aplikasi Optik dalam Teknologi Lensa Dan Kamera - Harta Setia Gea; Arianus Telaumbanua (CV. SINAR HOWUHOWU, 2024)
This research aims to analyze literature related to the application of optics in the development of lens and camera technology. Advances in optical technology have enabled significant improvements in image quality, such as sharpness, detail and color accuracy. The review covers various aspects of the innovation, including the use of high-quality materials, multi-element lenses, anti-reflective coatings, image stabilization, and autofocus techniques. This analysis also discusses applications of this technology in mobile devices, drones, and industrial applications. The study results show that innovations in optical technology play an important role in meeting users' demand for high-quality images, as well as expanding the potential of visual applications in various fields.